Our Nordic heritage: world heritage sites in the Nordic countries - Nordic World Heritage Office; Norwegian National Commission for UNESCO; UNESCO. Director-General, 1987-1999 (Mayor, F.). writer of preface; Anker, Leif (Kom Forlag, 1997)
Pref. by Federico Mayor, Director-General of UNESCO Incl. bibl. Pub. with the financial assistance of UNESCO.